Understanding Relationships Between Fetal Health Locus of Control (FHLC) and Maternal Marijuana Use During Pregnancy. (June 2022) - Murnan, Aaron; Keim, Sarah; Klebanoff, Mark
The objective of this study was to examine relationships between maternal perceptions of Fetal Health Locus of Control (FHLC) and perceived risk/benefit related to prenatal marijuana use with maternal marijuana use behaviors during pregnancy. The sample included women seeking prenatal care at The Ohio State University Wexner Medical Center (OSUWMC, Columbus OH) between 2010 and 2015, who participated in a follow-up study (2019–2020). Logistic regression models were run to estimate associations between maternal perceptions and prenatal marijuana use behaviors. Higher perceived benefit to mother (AOR = 1.53, 95% CI: 1.08–2.17) and lower perceived risk to children (AOR = 0.59, 95% CI: 0.45–0.78) were related to increased prenatal marijuana use, adjusted for confounders. In contrast, FHLC perceptions were not associated with maternal marijuana use; however, FHLC predicted women's perceptions of risk and benefit which in turn was associated with marijuana use during pregnancy. Understanding how maternal perceptions influence health-related risk behaviors during pregnancy is important because perceptions are feasible intervention targets.